(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Over the past decades, severe scoliosis cases were often treated with Halo traction prior to a single-stage correction and fusion surgery, which resulted in a prolonged operation, with many potential perioperative complications, posing a great challenge to both surgeons and anesthesiologists. Halo traction post posterior spinal release operation and followed by a second correction and fusion surgery has emerged as an effective alternative treatment method. Purpose: By clinical case, the two-stage surgical treatment is evaluated by result and literature review. Methods: Patient data has been collected preoperatively, perioperatively and postoperatively during hospital staying. Results: Our patient was a 14 years old female patient with severe double curves scoliosis and Von Recklinghausen syndrome. Stage one procedure prolonged 254 minutes with inferior articular process osteotomy and pedicle screw insertion; then, Halo traction maintained for 17 days. Stage two procedure was 190 minutes with posterior column osteotomy, correction and bone graft. Conclusion: The two stage surgical treatment method was applied and initially showed encouraging clinical and radiological results. However, long - term follow-up is essential.